Keselarasan Kompetensi Keterampilan Khusus pada Mata Kuliah Pengolahan Roti dengan KKNI Level 6 dan SKKNI - Fae Khansa Mora Iskandar; Guspri Devi Artanti; Annis Kandriasari (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze the alignment of sub-competences in the Bread-processing Course with the Indonesian Qualification Framwork Level 6 and the Indonesian National Work Competency Standard within the Culinary Education Study Program at Jakarta State University. For this research, qualitative approach is being used with descriptive analytic as the research method. Data were collected through direct observation in practicum session conducted involving 28 university students over 11 times practicum session. The findings indicate that the Bread-processing Course effectively develops student’ sub-competences in line with Indonesian Qualification Framework and Indonesian National Work Competency Standard. The practical implications suggest that the course curriculum and implementation are on the right path toward producing graduates whose skills meet the national occupation standards. However, to further strengthen the overall alignment, several areas can be enhanced to achieve far better optimal outcomes